2018
DOI: 10.1038/s41380-018-0082-9
|View full text |Cite
|
Sign up to set email alerts
|

Response to initial antipsychotic treatment in first episode psychosis is related to anterior cingulate glutamate levels: a multicentre 1H-MRS study (OPTiMiSE)

Abstract: Conventional antipsychotic medication is ineffective in around a third of patients with schizophrenia, and the nature of the therapeutic response is unpredictable. We investigated whether response to antipsychotics is related to brain glutamate levels prior to treatment. Proton magnetic resonance spectroscopy was used to measure glutamate levels (Glu/Cr) in the anterior cingulate cortex (ACC) and in the thalamus in antipsychotic-naive or minimally medicated patients with first episode psychosis (FEP, n = 71) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
118
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 74 publications
(91 reference statements)
15
118
4
1
Order By: Relevance
“…By using structural equation modeling, a significant pattern of increased glutamate levels in MZ cotwins compared with DZ co-twins and even more so compared with healthy controls was found in the left thalamus. The glutamate levels in the patients are comparable to those in MZ co-twins in the left thalamus but numerically lower in the ACC results in ACC since findings of increased glutamate or glx levels are reported in studies of a more ventral (pregenual) voxel [21,53], whereas unaltered metabolite levels are reported in a more dorsal voxel placement [19,20], similar to the one in the current study. In the ACC, we found no significant difference in glutamate or glx levels between groups but numerically the unaffected MZ cotwins had the highest concentration and patients had the lowest (see Figure S2 and S3 in Supplementary Material).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…By using structural equation modeling, a significant pattern of increased glutamate levels in MZ cotwins compared with DZ co-twins and even more so compared with healthy controls was found in the left thalamus. The glutamate levels in the patients are comparable to those in MZ co-twins in the left thalamus but numerically lower in the ACC results in ACC since findings of increased glutamate or glx levels are reported in studies of a more ventral (pregenual) voxel [21,53], whereas unaltered metabolite levels are reported in a more dorsal voxel placement [19,20], similar to the one in the current study. In the ACC, we found no significant difference in glutamate or glx levels between groups but numerically the unaffected MZ cotwins had the highest concentration and patients had the lowest (see Figure S2 and S3 in Supplementary Material).…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, the findings in the anterior cingulate cortex (ACC) are diverse. Here glutamate is found unaltered in antipsychotic naive [11,18] and minimally treated [17,19,20] patients with schizophrenia, but reports of increased glutamine levels in antipsychotic naive patients [11,18] are supported by findings of increased glx levels in the overlapping medial prefrontal cortical region of unmedicated patients ( [21,22]). Unaltered glutamine levels in first episode [23] and lower glx levels in antipsychotic naive patients [24] are also reported in prefrontal cortex.…”
Section: Introductionmentioning
confidence: 87%
“…Neuroimaging studies have suggested that treatment‐resistant schizophrenia may not show the dopaminergic dysfunction seen in treatment‐responsive schizophrenia, and that glutamatergic abnormalities may be of greater pathophysiological relevance in those cases of schizophrenia which do not respond to antipsychotic medications. Supporting this view, there is evidence that cortical glutamate levels are higher in patients with treatment‐resistant schizophrenia relative to responsive patients.…”
Section: Treatmentmentioning
confidence: 99%
“…However, there exists a range of novel mechanisms for manipulation of both glutamate and dopamine signalling that show potential and await clinical testing. As discussed above, it may be that certain treatments are only of benefit in specific subgroups of patients, and clinical benefit may therefore be optimized by stratifying participants on the basis of underlying neurobiology. Given the coarseness of current clinical measures, the development of imaging biomarkers to evaluate treatment effects at a neurobiological level may assist in moving the field forward.…”
Section: Outstanding Questions and Future Directionsmentioning
confidence: 99%
“…In The Lancet Psychiatry, Sudha Raman and colleagues 1 provide a rich summary of cross-national longitudinal trends in the prescription of central nervous system stimulant and non-stimulant attention deficit hyper activity disorder (ADHD) medications. They found the prevalence of ADHD medication in children aged 3-18 years in 2010 to be 0·95% in Asia and Australia, 4·48% in North America, 1·95% in northern Europe, and more research is warranted here in light of the positive correlation between anterior cingulate cortex glutamate concentration and symptom severity in a highly powered study of individuals with first-episode psychosis 5 and following a ketamine challenge, 6,7 the systematic evidence for raised MR spectroscopy indices of glutamatergic activity in psychosis, 6 and the preliminary observations suggesting that altered cortical glutamate function might be especially related to negative and cognitive symptom severity. 8 We believe that the interesting association between subcortical dopamine synthesis capacity, cortical glutamate, and psychotic symptoms reported by Jauhar and colleagues 1 warrants new research into the association between in vivo measures of neurotransmitter function and molecular mechanisms.…”
Section: Why Are Stimulant Medication Prescriptions Rising Globally?mentioning
confidence: 99%